On the type materials of the genera Interatherium Ameghino, 1887 and Icochilus Ameghino, 1889 (Interatheriidae, Notoungulata, Mammalia) from early Miocene of the Santa Cruz Province, Argentina - Fernández, Mercedes; Fernicola, Juan Carlos; Cerdeño, Esperanza (Zootaxa, 2019)
The first known Interatheriinae (Interatheriidae, Notoungulata) were described by Florentino Ameghino based on fossils collected by his brother Carlos in diverse Argentinean early Miocene outcrops in the Santa Cruz Province, which are housed at different institutions. In order to perform a systematic study of the subfamily, it is essential to revise as much specimens as possible, but first of all the type material of the species under study. Due to the fact that Florentino Ameghino never referred to any type specimens with a collection number in any of his publications, their identification becomes a complex task. In consequence, when studying the species erected by Ameghino within the genera Interatherium and Icochilus, we identified a lack of correspondence between some materials catalogued as type specimens and the original descriptions. In this contribution, we present the type specimens of 18 out of the 21 Santacrucian species of Interatherium (4) and Icochilus (14) within the paleontological collection of the Museo de La Plata and Ameghino National Collection at the Museo Argentino de Ciencias Naturales “Bernardino Rivadavia”. Four case studies are presented: a) specimens correctly identified; b) materials erroneously catalogued as type specimens; c) specimens catalogued as type, whose status cannot be evaluated because they are lost; and d) specimens not catalogued as types, but herein recognised as such. As the selection of the type species of Icochilus was pending, Ic. extensus is herein designated as such. The lectotypes of Ic. extensus and Ic. multidentatus are selected among their identified syntypes.